Growth, Yield and Seed Quality of Corn (Zea Mays L.) And Soybean (Glycine Max L. Merr.) As Affected by Population Density in Row - Prapto Yudono (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 1992)
-